An evaluation of a student-led career profiling project to support the exploration of a career in general practice and other specialties - Hannah Gyekye-Mensah; Arabella Watkins; Joseph Wenden; Imogen Horn; Jemimah Beardwood; Melvyn Jones; Emma Metters (BJGP Open, 2022)
Background: Choosing medical careers is complex but the undergraduate period is formative. St George’s University of London (SGUL) students called for greater careers information. Aim: To develop and evaluate students’ careers resources. Design & setting: A quality improvement student–staff project at SGUL, UK. Method: A ‘Plan-Do-Study-Act’ (PDSA) cycle was completed. For the ‘Plan’ element, students’ career intentions and information preferences were surveyed. For the ‘Do’ element, video interviews with clinicians and infographic posters were produced and published on SGUL’s virtual learning environment. For the ‘Study’ element, feedback questionnaires were thematically analysed using Kirkpatrick’s framework. For the ‘Act’ element, the model was rolled out across SGUL programmes. Results: In the ‘Plan’ stage, 79 students ranked interest in specialties, with general practice being the second most popular. Students were unconfident in how to pursue careers and wanted more information. For the ‘Do’ element, 13 careers videos and infographics were created for 10 specialties. The ‘Study’ questionnaire showed changes across three of the four levels in Kirkpatrick’s model of evaluation of training. Level 1 (Response): students found resources helpful and accessible. Level 2 (Learning): students reported increased understanding of careers. Level 3 (Transfer): students planned using checklists and made career comparisons by specialty. Level 4 (Results): students’ career choices were not demonstrated, but there were tentative proxy measures such as copying and modelling career routes and choices. ‘Act’ involved rolling out and regularly updating resources. Conclusion: This PDSA model enabled development of resources by students mapped to students’ needs. Changes were demonstrated in relation to students’ response, learning, and transfer, with tentative suggestions of impact on career choice.